The cross-cultural issues in the process of teaching English as a second language - Potemkina Victoria; Zhao Junning (Bandar Lampung University (UBL), 2013)
Nowadays it is not enough to be just a good professional teacher, one should also research new teaching methods and approaches as well as combine different school disciplines in the educational process.One of the innovative approaches was implemented in Shanghai Foreign Language School. On the lessons of ESL with a group of schoolchildren (returnees) were used “The analects” by Confucius, furthermore the parents got involved in the educational process. Bilingual method of teaching isn’t something new nowadays but using the classical Chinese educational source in teaching ESL is ultimately innovative method.